2018
DOI: 10.1678/rheology.46.23
|View full text |Cite
|
Sign up to set email alerts
|

Stress Undershoot of Entangled Polymers under Fast Startup Shear Flows in Primitive Chain Network Simulations

Abstract: In this study, viscosity growth of entangled polymers under startup of fast shear flows was investigated by means of primitive chain network simulations. In particular, we focused on the undershoot following the well-known overshoot. The simulations reasonably reproduced the viscosity growth data reported in the literature for polystyrene melts. To investigate the origin of the observed undershoot, stress was decomposed into orientational and stretch contributions through a decoupling approximation. The decoup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
4
14
1
Order By: Relevance
“…They examined segmental orientation, tube stretch, and the ensemble average squared sine of the chain end-to-end orientation angle (representing the tumbling motion) and showed that all these variables exhibit undershoots, although not synchronized with shear stress. Masubuchi et al [43] concluded that their results supported the mechanism proposed by Costanzo et al [16]…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…They examined segmental orientation, tube stretch, and the ensemble average squared sine of the chain end-to-end orientation angle (representing the tumbling motion) and showed that all these variables exhibit undershoots, although not synchronized with shear stress. Masubuchi et al [43] concluded that their results supported the mechanism proposed by Costanzo et al [16]…”
Section: Resultssupporting
confidence: 61%
“…This may be due to the relatively low entanglement density of the C 400 H 802 molecules used in their NEMD simulations. Masubuchi et al [43] also investigated the origin of the stress undershoot at high shear rates using primitive chain network simulations. They examined segmental orientation, tube stretch, and the ensemble average squared sine of the chain end-to-end orientation angle (representing the tumbling motion) and showed that all these variables exhibit undershoots, although not synchronized with shear stress.…”
Section: Resultsmentioning
confidence: 99%
“…(G 0 is thermal energy per unit volume.) The parameters are insensitive to flow and deformation [15,35,38,57,[60][61][62][63][64].…”
Section: Model and Simulationsmentioning
confidence: 99%
“…Masubuchi et al [33] reproduce the probe rheology data reported by Matsumiya et al [30] using primitive chain network (PCN) model, which describes the dynamics of the network formed by the primitive chains and is used extensively in literature [34][35][36][37][38]. Their results agree with the experiment well.…”
Section: Introductionmentioning
confidence: 62%